Solid ectopic cervical thymus in an infant - Vlahović, Aleksandar; Živković, Milana; Majić, Velibor; Badnjar-Ilić, Zorka; Begović, Ninoslav; Dizdarević, Ivan (Vojnosanitetski pregled, 2023)
Introduction. Ectopic cervical thymus (ECT) occurs as a result of incomplete migration of the thymic primordia during embryogenesis. In the majority of cases, ECT is asymptomatic; however, in 10% of patients, there are different kinds of symptoms. Case report. A four-month-old baby boy was referred to our clinic for an evaluation of a growing large mass on the right side of the neck, present since birth. Physical examination revealed a solid, painless, soft, moderately mobile mass of irregular round shape localized on the right side of the neck, in front of the sternocleidomastoid muscle, below the parotid gland, and above the carotid lodge. The skin above the mass was unchanged. The dimensions of the mass were 40 × 32 × 15 mm. Based on the clinical and ultrasonographic findings, as well as the findings of the magnetic resonance imaging, it was suspected that the mass was an ECT. The mass was removed by surgical excision. The pathohistology report confirmed the presence of an ECT, with Hassall’s corpuscles in the medulla. The postoperative course went smoothly, and the wound healed well. During the regular clinical, immunological, and ultrasound follow-ups over a period of six months, normal findings were registered. Conclusion. Congenital ECT is a rare congenital anomaly that must be, however, taken into account when considering the differential diagnosis of cervical tumor masses.